2010
DOI: 10.1007/s00421-010-1784-0
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric stimulation reveals an involvement of FGF6 in muscle resistance to mechanical stress

Abstract: The objective of this report was to analyse a potential role for FGF6 in muscle resistance to mechanical stress. Normal or regenerating muscles of FGF6 (-/-) mice versus wild-type mice were submitted to different protocols of damaging eccentric contractions (eccentric electrostimulation and intermittent downhill exercise). Then muscular structural properties were analysed by histological and immunochemistry techniques to evaluate the post-injury muscle recovery; their muscle contractile parameters (maximal tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Phosphorylation of FOXO proteins by IGF1 downregulates Murf1 and MAFbx [26] and transcripts for MAFbx had decreased 20-30-fold to almost undetectable levels by 16 h (Figure 3A). Studies in mammals suggested that FGF6 expression regulates muscle differentiation and the maintenance of muscle integrity during mechanical stress [27]. FGF6 showed rapid (<24 h) and transitory increases with SF (Figure 3E).…”
Section: Discussionmentioning
confidence: 95%
“…Phosphorylation of FOXO proteins by IGF1 downregulates Murf1 and MAFbx [26] and transcripts for MAFbx had decreased 20-30-fold to almost undetectable levels by 16 h (Figure 3A). Studies in mammals suggested that FGF6 expression regulates muscle differentiation and the maintenance of muscle integrity during mechanical stress [27]. FGF6 showed rapid (<24 h) and transitory increases with SF (Figure 3E).…”
Section: Discussionmentioning
confidence: 95%